Analyzing the Threshold Relationship between Public Debt and Economic Growth in New EU Member States from Central and South Eastern Europe - Petkovski, Mihail; Stojkov, Aleksandar; Kjosevski, Jordan (Ekonomický časopis, 2024)
This paper examines the relationship between public debt and economic growth in 11 new EU member states (NMS) from Central and South Eastern Europe during 2000–2021. The authors explore the potential non-linear (quadratic) nature of this relationship, accounting for heterogeneity by dividing the NMS into three subgroups: South Eastern European, Baltic, and Visegrad countries. Findings suggest a U-inverted relationship, where public debt positively affects growth up to a threshold, beyond which a negative effect prevails. The estimated debt-to-GDP tipping point ranges from 58.5% to 73.5%, depending on the subgroup. The results offer insights for designing a new EU fiscal rules framework.